COVID-19 and Pregnancy Outcome: An Experience in ‘COVID-19 Management Designated’ Tertiary Care Hospital, Rawalpindi, Pakistan - Shazia Syed ,Humera Noreen ,Humaira Masood ,Ismat Batool ,Hina Gul ,Nighat Naheed (Journal of Rawalpindi Medical College, 2020)
Background: The current COVID-19 pandemic has affected almost 17.3 million victims worldwide with mortality of almost 674K. Pregnancy is one of the most susceptible conditions for COVID-19 infection, but limited data is currently available about the clinical characteristics of pregnant women with the disease. Objective; to describe the clinical characteristics, co-morbidities, management, feto-maternal, and neonatal outcome in COVID-19 positive pregnant women. Methodology: A descriptive case series study was conducted in Obs/Gynae dept of Benazir Bhutto Tertiary Care Hospital, Rawalpindi, including all asymptomatic/symptomatic COVID-19 positive pregnant women and clinical suspects (COVID-19 PCR negative women) delivered in our hospital from 01st April 2020 to 31st July 2020. Their medical records were reviewed for clinical characteristics, management, feto-maternal and neonatal outcomes. Continuous variables were expressed in Mean & Range and Categorical variables as number & Percentage. Results: During the study period a total of 17 cases were reviewed. The mean maternal age was 28.94 yrs. Primigravida (07), Multipara (10). Mean gestational age was 37 wks (range; 30-41wks). Presenting symptomatology was varied. Asymptomatic; (29%), COVID-19 specific symptoms; fever & flu (12%), fever&cough (6%), shortness of breath(SOB) alone (6%), fever & SOB(6%) and pregnancy-related manifestations were labour pains (17%), eclampsia(6%), hydrocephalous fetus (6%) and hepatic encephalopathy(6%). The commonest co-morbidity was Hypertensive disorders of pregnancy (24%). Five women (29%) required ICU care. Lower segment caesarean sections(LSCS) (59%), vaginal delivery (41%). Eleven babies delivered with good Apgar score and birth weight. Two were early neonatal deaths (ENND) and 04 were received intra-uterine fetal deaths (IUDs). Fetal demise was associated with strong obstetric risk factors. Out of 13 live-born babies, RT-PCR Covid-19 testing was done in 10 (77%) cases and was negative. One mother was expired due to complications of hepatic encephalopathy, sepsis, and burst abdomen. Conclusion; The clinical course of COVID-19 disease in pregnancy seems to be no different from non-pregnant women. Clinical manifestations are diverse and infection contracted in the third trimester of pregnancy is associated with good feto-maternal and neonatal outcomes.